Ocorrência de Escherichia coli produtoras de Klebsiella pneumoniae carbapenemase (KPC) em Psittaciformes resgatados do tráfico de animais na Paraíba. - Silva, Gedean Galdino da Cruz (2019)
Bacterial resistance is one of the greatest challenges worldwide and wild birds in this context, becoming potent sources of dissemination of multiresistant bacteria. The objective of this work was to report the occurrence of KPC - producing Escherichia coli in Psittaciformes rescued from the trafficking of wild animals in the state of Paraíba. For this, swabs of the cloacal microbiota of ten Turquoise-fronted Parrot (Amazona aestiva), two Orange-winged Parrot (Amazona amazonica), one Festive Parrot (Amazona festiva), three Blue-and-yellow Macaw (Ara ararauna), three Red-and-green Macaw (Ara chloropterus), Scarlet Macaw (Ara macaw), five Red-shouldered Macaw (Diopsittaca nobilis), one Peach- fronted Parakeet (Eupsittula aurea), one Cactus Parakeet (Eupsittula cactorum), one Blue- winged Parrotlet (Forpus xanthopterygius), one White-eyed Parakeet (Psittacara leucophthalmus) and one Blue-crowned Parakeet (Thectocercus acuticaudatus), were collected in duplicate and packed in glass tubes containing 4 mL each of MacConkey broth and STGG - Skim Milk, Tryptone, Glucose and Glycerin, for further culture in MacConkey medium plus antimicrobials: (i) Ceftriaxone 8 μg / mL; (ii) imipenem 1 μg / mL and (iii) polymyxin B 3.5 μg / mL. Then, the isolates were identified through phenotypic tests (TSI - Triple Sugar Iron Agar, LIA - Lysine Iron Agar, urea, phenylalanine and MIO - Motidad, Indol, Ornithine), for subsequent determination of antimicrobial susceptibility profile: sulfazotrim 25MCG; ertapenem 10MCG; meropenem 10MCG; imipenem 10MCG; amikacin 30MCG; ciprofloxacin 5MCG; tetracycline 30MCG; chloramphenicol 30MCG; ceftriaxone 30MCG; ceftazidime 30MCG; ampicillin + sulbactam 20MCG; aztreonam 30MCG and amoxicillin + clavulanic acid 30MCG, through the disc diffusion method on Mueller-Hilton agar, through the Muller-Hilton agar diffusion method, according to CLSI (Clinical & Laboratory Standards Institute) recommendations. In addition, we performed the phenotypic disc-approximation test for the detection of ESBL (Extended-spectrum β-lactamase). In order to identify genes coding for resistance to betalactamases (CTX-M), carbapenemases (NDM and KPC) and colistin (MCR-1), the isolates were also submitted to PCR (Polymerase chain reaction) technique and typing of the samples was performed by REP-PCR (Repetitive Extragenic Palindromic Sequence based PCR). Of the 30 animals collected 19 (63.3%) presented bacterial growth in at least one of the culture media supplemented with antimicrobials. In relation to the positive samples, 18 (60%) of them originated from MacConkey broth and 11 (36.6%) STGG broth. Of the 60 colonies isolated 43 (71.7%) belonged to the species Escherichia coli. Regarding the interpretation of antibiograms, ciprofloxacin presented the highest prevalence of resistant strains. No samples were positive for ESBL detection. Of the genes encoding resistance tested only the blaKPC was found in thirteen isolates of seven individuals, these four being from different strains and eight strains clones. In this way, the relevance of the monitoring of these species is clear, due to the presence of antimicrobial resistant isolates used in the clinical treatment of human and veterinary bacterioses. In addition, the work showed that members of the Enterobacteriaceae family present in the cloacal microbiota of captive wild birds can carry important resistance - encoding genes such as KPC, being the first record of the gene in the order Psittaciformes in the state of Paraíba - Brazil.